THE INFLUENCE OF SCHOOL DIGITAL COMMUNICATION ON PARENTAL SATISFACTION AND LOYALTY IN PRIMARY SCHOOL - Asih Anjarwati; Gunawan (SOSIOEDUKASI, 2026)
This study aims to examine the influence of digital communication carried out by schools on the level of parental satisfaction and loyalty at the elementary school level and to find out the correlation between parental satisfaction and parental loyalty. The approach used is quantitative with a survey approach. The population used was parents or guardians of students in Cilacap sub-district with a research sample of parents whose children were schooled in public schools. The sampling technique is stratified random sampling. The data collection technique carried out was a questionnaire consisting of a school digital communication questionnaire, a satisfaction questionnaire, and a parent loyalty questionnaire. The data analysis technique used the SPSS application with a simple regression test and a Pearson correlation test. The results of the study show that school digital communication has a significant influence on parental satisfaction and loyalty. In addition, parental satisfaction has been shown to have a strong and significant relationship in increasing their loyalty. These findings suggest that the implementation of effective digital communication can increase parental satisfaction, which in turn has implications for increased loyalty to schools. There is a reciprocal relationship, where increased parental loyalty also contributes to strengthening satisfaction with services and the quality of learning in primary schools